2014
DOI: 10.2478/s11686-014-0253-z
|View full text |Cite
|
Sign up to set email alerts
|

The parasitic fauna of the European bison (Bison bonasus) (Linnaeus, 1758) and their impact on the conservation. Part 2 The structure and changes over time

Abstract: During the last century the recorded parasite fauna of Bison bonasus includes 88 species. These are 22 species of protozoa, 4 trematode species, 4 cestode species, 43 nematode species, 7 mites, 4 Ixodidae ticks, 1 Mallophaga species, 1 Anoplura, and 2 Hippoboscidae flies. There are few monoxenous parasites, the majority of parasites are typical for other Bovidae and Cervidae species and many are newly acquired from Cervidae. This is an evident increased trend in the parasite species richness, in both the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Apart from small herd size, isolation and low genetic variation due to a severe genetic bottleneck after extinction in the wild (Tokarska et al 2011), diseases and parasites (Pucek et al 2004) are the main threats to bison. Among the 88 parasite species discovered in European bison (Dróżdż et al 1998; Karbowiak 2014a, b), the blood-sucking nematode Ashworthius sidemi is probably the most pathogenic. This parasite is specific to Asian deer species, especially sika deer ( Cervus nippon ) (Dróżdż et al 1998) and was first found in bison from Białowieża Forest (BF) in 2000 (Kołodziej-Sobocińska et al 2016a).…”
mentioning
confidence: 99%
“…Apart from small herd size, isolation and low genetic variation due to a severe genetic bottleneck after extinction in the wild (Tokarska et al 2011), diseases and parasites (Pucek et al 2004) are the main threats to bison. Among the 88 parasite species discovered in European bison (Dróżdż et al 1998; Karbowiak 2014a, b), the blood-sucking nematode Ashworthius sidemi is probably the most pathogenic. This parasite is specific to Asian deer species, especially sika deer ( Cervus nippon ) (Dróżdż et al 1998) and was first found in bison from Białowieża Forest (BF) in 2000 (Kołodziej-Sobocińska et al 2016a).…”
mentioning
confidence: 99%
“…commun.). According to other blood-sucking parasites, hookworms have never been noted in European bison (Karbowiak et al 2014a(Karbowiak et al , 2014b. Although two species of blood-sucking nematodes were recorded in large intestine (Bunostomum trigonocephalum and Trichuris ovis) of bison but in low infection intensity (Demiaszkiewicz et al 2012), so we can assume that the possibility of other haematophagous parasites influencing the observed pattern was not significant.…”
Section: Resultsmentioning
confidence: 99%
“…Bison have been parasitologically investigated and monitored with different intensity since their reintroduction to the wild in 1952 (Dróżdż 1961). A total of 88 species of parasites have already been discovered in bison, and there is an increasing trend in species richness as well as the prevalence and intensity of infections (Karbowiak et al 2014a(Karbowiak et al , 2014b. Recently, the blood-sucking nematode Ashworthius sidemi (Trichostrongylidae) has been assimilated within the abomasa of European bison.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing trend in parasite species richness as well as the prevalence and intensity of infections. This could be caused by possible transmission from other ruminants or the increased contact rate between bison in winter due to their high density arising from supplementary feeding in fixed locations (Karbowiak et al 2014b;Radwan et al 2010;Pyziel et al 2011). It is known that European bison are infested with parasite larvae through contact with contaminated water and pastures (Treboganova 2010).…”
Section: Discussionmentioning
confidence: 99%